Hyper-realistic and immersive surgical simulation training environment will improve team performance. Issue 1 (10th March 2020) - Hoang, Tuan N; LaPorta, Anthony J; Malone, John D; Champagne, Roland; Lavell, Kit; De La Rosa, Gabriel M; Gaul, Lawrence; Dukovich, Mitchell
Abstract : Background: Surgical trauma care requires excellent multidisciplinary team skills and communication to ensure the highest patient survival rate. This study investigated the effects of Hyper-realistic immersive surgical team training to improve individual and team performance. A Hyper-realistic surgical training environment is defined as having a high degree of fidelity in the replication of battlefield conditions in a training environment, so participants willingly suspend disbelief that they become totally immersed and eventually stress inoculated in a way that can be measured physiologically. Methods: Six multispecialty member US Navy Fleet Surgical/US Army Forward Surgical Teams (total n=99 evaluations) underwent a 6-day surgical training simulation using movie industry special effects and role players wearing the Human Worn Surgical Simulator (Cut Suit). The teams were immersed in trauma care scenarios requiring multiple complex interventions and decision making in a realistic, fast-paced, intensive combat trauma environment. Results: Hyper-realistic immersive simulation training enhanced performance between multidisciplinary healthcare team members. Key efficacy quantitative measurements for the same simulation presented on day 1 compared with day 6 showed a reduction in resuscitation time from 24 minutes to 14 minutes and critical error decrease from 5 to 1. Written test scores improved an average of 21% (Medical Doctors 11%, Registered Nurses 25%, and Corpsman/Medics 26%). Longitudinal psychometric survey results showed statistically significant increases in unit readiness (17%), combat readiness (12%), leadership quality (7%), vertical cohesion (7%), unit cohesion (5%), and team communication (3%). An analysis of salivary cortisol and amylase physiologic biomarkers indicated an adaptive response to the realistic environment and a reduction in overall team stress during performance evaluations. Conclusions: Hyper-realistic immersive simulation training scenarios can be a basis for improved military and civilian trauma training. Level of evidence: Level III.